The Influence of Organizational Culture, Work Environment and Work Motivation on Employee Performance of PT Perkebunan Nusantara IV Medan - Sheryl Hisara Ambardi Siahaan; Edi Putra Berutu; Sondang Beatrix Siahaan (CERED Indonesia Institute, 2023)
This research aims to determine the influence of Organizational Culture, Work Environment and Work Motivation on Employee Performance at the Head Office of PT Perkebunan Nusatara IV Medan. This type of research is quantitative research. The population used in this research was 290 employees of the head office of PT Perkebunan Nusantara IV Medan. The number of respondents consisted of 168 people, with sample determination using the Slovin formula. The results of this research show that Organizational Culture, Work Environment and Work Motivation have a significant and influential effect on the performance of PT Perkebunan Nusantara IV Medan Head Office employees, both partially and simultaneously. The results of the R square research show that the variables Organizational Culture, Work Environment and Work Motivation influence employee motivation by 2.